The importance of infertility duration and follicle size according to pregnancy success in women undergoing ovulation induction with gonadotropins and intrauterine insemination - Meryem Kuru Pekcan; Aytekin Tokmak; Hasan Ulubasoglu; Mervenur Kement; Gülnur Özakşit (Taylor & Francis Group, 2023)
In this study, we aimed to evaluate the effect of infertility duration and dominant follicle size measured on the day of human chorionic gonadotropin (HCG) administration on pregnancy rates in infertile women undergoing ovulation induction (OI) with gonadotropin (GND). A total of 352 patients aged 20 to 41 years who were diagnosed with unexplained infertility or polycystic ovary syndrome (PCOS) were included in this study. Patients with a history of multifollicular development or follicle stimulating hormone (FSH) value more than 12 IU/ml were excluded from the study. The demographic and clinical features of the patients were obtained from the patients' files and hospital automation system and recorded for each woman. The demographic and clinical features of the patients were recorded. Patients were divided into two groups as live birth (group 1, n = 47) and non-live birth groups (group 2, n = 305). There were no statistically significant differences in regard to age, infertility type, follicle stimulating hormone (FSH) level, oestradiol (E2) level, antral follicle count (AFC), cycle characteristics, GND type, number of follicles, E2 level and endometrial thickness on HCG day, total GND dose, dominant follicle size (p > 0.05). Infertility duration in group 1 was 3.5 ± 2.1; in group 2, 4.7 ± 3.9 years. This difference was statistically significant (p = .014). According to this study, live birth rates after GND + IUIs(intrauterine insemination) were significantly affected by the duration of infertility. But the dominant follicle size and endometrial thickness measured on HCG day in GND and IUI cycles did not have a significant effect on pregnancy rates.IMPACT STATEMENT What is already known on the subject? It is thought that the timing of the ovarian triggering is vital for the success of intrauterine insemmination (IUI) treatment. What do the results of this study add? According to our results live birth rates after GND + IUIs were significantly affected by the duration of infertility. What are the implications of these findings for clinical practice and/or further research? It is determined that the duration of infertility is significant and patients should be encouraged to the treatment as soon as possible.